Performance Management Control Change And Integration In The Central Government Of Malaysia - George, Roshni Ann (2022)
Although public management systems in Malaysia have been transforming over the years, improvement initiatives have not resolved performance management issues. These issues may persist due to problems in performance management control integration. Therefore, the purpose of this qualitative case study, conducted in several national ministries and agencies, was to explore how performance management control change impacted performance management control integration within the central government of Malaysia. Data collection involved extensive semi-structured interviews, documentation on performance management control processes and non-participant observations. Drawing on strong structuration theory, key themes related to performance management control change and stability were identified in this study. The interplay between structure and agency was examined by delving into agent conduct and context analysis. The implementation of a new outcome based budgeting system resulted in certain tensions between drivers and implementers, impeding strong performance management control integration. Despite gradual changes to the budgeting system, the situated rationalities of implementers remained relatively unchanged. The study has found that performance management controls in the public sector often operate in silos. Gaps in integration could be closed if there are more robust budgeting, monitoring and evaluation practices linked to existing planning structures.